Reexamining the Wage, Tenure and Experience Relationship - Williams, Nicolas (The Review of Economics and Statistics, 1991)
Despite considerable empirical research, a debate still rages about the relative importance of tenure and experience in determining wages given the existence of unobserved heterogeneity. Using a data set well suited to this problem, the author finds after correcting for unobserved heterogeneity that tenure increases wages only in the first several years of employment. The accumulated effect of general labor-market experience increases wages substantially over the career. This evidence suggests that specific human capital accumulation is relatively less important than some might believe. This result is robust to different estimation techniques that have been suggested in the literature. Copyright 1991 by MIT Press.